Formulation of a Dynamic Portfolio With Stocks and Fixed-income Instruments in the Indonesian Capital Market - Robiyanto, Robiyanto; Ernayani, Rihfenti; Ismail, Rendi Susiswo (Organizations and Markets in Emerging Economies, 2019)
This research creates a crossed asset portfolio formulation dynamically with stocks and fixed-income instruments. This dynamic portfolio formulation did not require normally distributed data and accommodated the correlation among class assets which kept changing across time. This was based on the existing assumptions in the modern portfolio theory which were rarely found in the real world, for example, when stock return was normally distributed, the correlation among securities would be constant at all times. The data used in this research were LQ45 Index as a stock market proxy, S&P Indonesia Corporate Bond Index (representing the corporate bond market) and S&P Indonesia Government Bond Index data (representing the government bond market) during the period of June 4th, 2007 to April 11th, 2016. This research found that the dynamic portfolio of stock with either government or corporate bonds was able to reduce the level of risk significantly despite producing a lower rate of return, compared to the ones specifically invested in the stock market. Investors who believe in the principles of prudent investment may use this dynamic approach in shaping the portfolio with stocks and fixed-income instruments.